An action plan for Europe's leaders - Benedicta Marzinotto; Jean Pisani-Ferry; Guntram B. Wolff (Bruegel, 2011)
At the extraordinary EU Council of 21 July European leaders have to accomplish a triple-mission. First, they should pave the way to restoring solvency in Greece by initiating debt reduction. Softening the Greek debt burden implies i) reducing the interest rate on official lending, ii) requesting from the EFSF support for an immediate bond buy-back programme, and iii) asking the ESRB for an immediate evaluation of the risks to financial stability involved in a future restructuring of the sovereign debts in the euro area. Second, they should promote immediate growth-enhancing measures to be financed through unused EU structural funds and EIB loans (16bn). The available funds shall be used to i) raise the quality of higher education, ii) finance wage subsidies in manufacturing and tourism so as to generate an internal devaluation at contained domestic-demand costs; and ii) create research laboratories (i.e. lighthouse innovation projects) that would support an upgrading of the Greek value chain. Third, they should address risks to financial stability in the euro zone by breaking the vicious circle between sovereign debt and banking risk. The EFSF should be able to guarantee national deposit insurance schemes; at the same time, the European Banking Authority should assume stronger supervisory powers. This is an immediate action plans but of course more ambitious reforms are necessary down the road.
Keywords: 330; EU-Politik; Politisches Ziel; Öffentliche Schulden; Wachstumspolitik; Bankenkrise; Krisenmanagement; EU-Staaten